ANALISIS PENGELOLAAN LEMBAGA ZAKAT MUHAMMADIYAH DALAM PEMBERDAYAAN EKONOMI UMAT DI MASA PANDEMI COVID 19 - DZAKY EL KEMAL, SAIEV; AYUNIYYAH, QURROH; ERISMEN ARMEN, RIO (Kasaba, 2023)
The COVID-19 pandemic has had a lot of impact on human life in general. Various problems one by one began to arise and became a burden in the community. The economic and social fields are the fields that have been affected quite a lot during this pandemic. This research discusses how to get out of this pandemic crisis by using Islamic philanthropic instruments, namely zakat and its derivatives such as infak and almsgiving to be able to prosper people in need, especially during this pandemic. Through social programs owned by the Muhammadiyah zakat infak and shadaqah institution or (LAZISMU) the city of Surakarta is expected to be able to meet the needs and welfare of the community during the pandemic. This type of research is field research. The method used in this study is descriptive-qualitative by using primary data sources and secondary data collected by means of documentation, interviews and literature studies. The results of this study are the first, LAZISMU Surakarta City has managed people's funds in accordance with applicable regulations with several innovations that are allowed to be carried out. Second, The Social Program is a model of empowerment that is consumptive in nature. It has advantages and disadvantages, including being very beneficial for the community when the number of COVID-19 pandemic cases is increasing, as for when the number of cases begins to decline, what is expected by the community is another empowerment model that is productive in nature. Third, the impact of economic empowerment of the people carried out by LAZISMU Surakarta through the Social Program only benefits the community in the form of assistance that is temporary effect not long-term.